Fostering digital literacy in the elderly as a means to secure their health needs and human rights in the reality of the twenty-first century - Susło, Robert; Paplicki, Mateusz; Dopierała, Karol; Drobnik, Jarosław (Family Medicine & Primary Care Review, 2018)
The rights to life and health are basic human rights but, as life spans increase and societies age, these rights become increasingly difficult to secure. The number of people needing care, nursing, and medical treatment increases – and their expectations of quality of life rise – faster than the available financial assets and workforce. The article aims at defining the influence of digital literacy of patients and digital-based medical services availability on perspectives of fulfilling health-related needs specific for ageing societies. A variety of information and communication technologies (ICT) solutions can deliver at least temporary relief to countries suffering from these problems, assuming that the potential beneficiaries are able and willing to use such methods. It is thus worthwhile to foster digital literacy, especially among middle-aged and older people. ICT-based solutions include a variety of more or less technologically advanced, sophisticated, and easy-to-use services, many of which have been in operation and common use for decades, and are thus ripe for medical application. Such technologies can create a highly complex system of interconnected electronic tools and information systems operating on sensitive medical data that must remain confidential. These systems aim to increase patients’ medical safety and maximize their quality of life, but they also pose serious threats to their privacy. Confidential data are protected by legal regulations, including the recently introduced European General Data Protection Regulation (GDPR), but primary care physicians should not be discouraged by this from implementing ICT-based solutions into their practices, as they may significantly lessen their everyday workload.